Action of soil microorganisms on PCL and PHBV blend and films - Goncalves, S. P. C. [UNESP]; Martins-Franchetti, S. M. [UNESP] (Springer/plenum Publishers, 2010)
Poly(hydroxybutyrate-co-valerate) (PHBV) and poly(epsilon-caprolactone) (PCL) PCL/PHBV (4:1) blend films were prepared by melt-pressing. The biodegradation of the films in response to burial in soil for 30 days was investigated by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and thermogravimetry (TG). The PHBV film was the most susceptible to microbial attack, since it was rapidly biodegraded via surface erosion in 15 days and completely degraded in 30 days. The PCL film also degraded but more slowly than PHBV. The degradation of the PCL/PHBV blend occurred in the PHBV phase, inducing changes in the PCL phases (interphase) and resulting in an increase of its crystalline fraction.
Keywords: Biodegradation; Blend; FTIR; DSC; TG